Feed thickener for infants up to six months of age with gastro-oesophageal reflux (Review) - Kwok, T'ng Chang; Ojha, Shalini; Dorling, Jon (Wiley, 2017)
Background Gastro-oesophageal reflux (GOR) is common in infants, and feed thickeners are often used to manage it in infants as they are simple to use and perceived to be harmless. However, conflicting evidence exists to support the use of feed thickeners. Objectives To evaluate the use of feed thickeners in infants up to six months of age with GOR in terms of reduction in a) signs and symptoms of GOR, b) reflux episodes on pH probe monitoring or intraluminal impedance or a combination of both, or c) histological evidence of oesophagitis. Search methods We used the standard search strategy of the Cochrane Neonatal Review Group to search the Cochrane Central Register of Controlled Trials (CENTRAL 2016, Issue 2), MEDLINE via PubMed (1966 to 22 November 2016), Embase (1980 to 22 November 2016), and CINAHL (1982 to 22 November 2016). We also searched clinical trials databases, conference proceedings, and the reference lists of retrieved articles for randomised controlled trials. Selection criteria We included randomised controlled trials if they examined the effects of feed thickeners as compared to unthickened feeds (no treatment or placebo) in treating GOR in term infants up to six months of age or six months of corrected gestational age for those born preterm. Data collection and analysis Two review authors independently identified eligible studies from the literature search. Two review authors independently performed data extraction and quality assessments of the eligible studies. Differences in opinion were resolved by discussion with a third review author, and consensus was reached among all three review authors.We used the GRADE approach to assess the quality of the evidence. Main results Eight trials recruiting a total of 637 infants met the inclusion criteria for the systematic review. The infants included in the review were mainly formula-fed term infants. The trials were of variable methodological quality. Formula-fed term infants with GOR on feed thickeners had nearly two fewer episodes of regurgitation per day (mean difference -1.97 episodes per day, 95% confidence interval (CI) -2.32 to -1.61; 6 studies, 442 infants, moderate-certainty evidence) and were 2.5 times more likely to be asymptomatic from regurgitation at the end of the intervention period (risk ratio 2.50, 95% CI 1.38 to 4.51; number needed to treat for an additional beneficial outcome 5, 95% CI 4 to 13; 2 studies, 186 infants, low-certainty evidence) when compared to infants with GOR on unthickened feeds. No studies reported failure to thrive as an outcome. We found low-certainty evidence based on 2 studies recruiting 116 infants that use of feed thickeners improved the oesophageal pH probe parameters of reflux index (i.e. percentage of time pH < 4), number of reflux episodes lasting longer than 5 minutes, and duration of longest reflux episode. No major side effects were reported with the use of feed thickeners. Information was insufficient to conclude which type of feed thickener is superior. Authors’ conclusions Gastro-oesophageal reflux is a physiological self resolving phenomenon in infants that does not necessarily require any treatment. However, we found moderate-certainty evidence that feed thickeners should be considered if regurgitation symptoms persist in term bottle-fed infants. The reduction of two episodes of regurgitation per day is likely to be of clinical significance to caregivers. Due to the limited information available, we were unable to assess the use of feed thickeners in infants who are breastfeeding or preterm nor could we conclude which type of feed thickener is superior.